1986
DOI: 10.1007/bf02035056
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound study of adenopathies within the hepatoduodenal ligament: The “rosebud” pattern

Abstract: In about 10% of lymphopathies with extensive retroperitoneal adenopathies, adenopathies are also encountered within the hepatoduodenal ligament. When large, such adenopathies, which surround the portal vein, hepatic artery, and bile duct, give rise to a particular ultrasound pattern: the "rosebud pattern."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Lymphatic channels in the hepatoduodenal ligament receive lymph from the liver, gallbladder, bile ducts, duodenum, stomach, and pancreas and drain into the paraaortic ganglia near the origin of the superior mesenteric artery. 3 In previous studies, enlarged lymph nodes were observed in the hepatoduodenal ligament in patients with chronic viral hepatitis at varying frequencies (45-100%), which indicated differences in the true status of the lymph node, in the resolution of sonography, and in the technique of the sonographers 20 ; these findings were also confounded by many possible causes. We excluded patients with biliary and pancreatic disease, chronic nonviral liver disease, known malignancy, or other inflammatory processes around the hepatoduodenal ligament to eliminate these confounding factors and to clarify the nodal presentations of subjects with HBV or HCV infection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lymphatic channels in the hepatoduodenal ligament receive lymph from the liver, gallbladder, bile ducts, duodenum, stomach, and pancreas and drain into the paraaortic ganglia near the origin of the superior mesenteric artery. 3 In previous studies, enlarged lymph nodes were observed in the hepatoduodenal ligament in patients with chronic viral hepatitis at varying frequencies (45-100%), which indicated differences in the true status of the lymph node, in the resolution of sonography, and in the technique of the sonographers 20 ; these findings were also confounded by many possible causes. We excluded patients with biliary and pancreatic disease, chronic nonviral liver disease, known malignancy, or other inflammatory processes around the hepatoduodenal ligament to eliminate these confounding factors and to clarify the nodal presentations of subjects with HBV or HCV infection.…”
Section: Discussionmentioning
confidence: 93%
“…2 Hence, lymph nodes depicted in the hepatoduodenal ligament were considered malignant. 3 Abdominal lymphadenopathy attributed to benign reactive hyperplasia was first reported in autopsy studies of individuals who had used heroin or opiates 4,5 and on sonographic examinations of individuals who abused drugs. 6 Forsberg and colleagues 7,8 first emphasized this phenomenon in nonmalignant hepatobiliary disease, especially chronic immunomediated liver disease.…”
mentioning
confidence: 99%
“…Several variations in this relation can occur, some of which are due to aberrant and accessory hepatic arteries. Lymphatic channels in the hepatoduodenal ligament drain the liver, gallbladder, bile ducts, duodenum, stomach, and pancreas into the paraaortic nodes near the origin of the superior mesenteric artery (2). The nerves that course through the porta hepatis are branches of the left vagus nerve and sympathetic branches of the celiac plexus.…”
Section: Radiologic Anatomymentioning
confidence: 99%
“…Lymphatic channels in the HDL drain the liver, gallbladder, bile ducts, duodenum, stomach, and pancreas into the paraaortic nodes near the origin of the superior mesenteric and celiac artery. [ 13 ] Typical nodes are the hilar node, cystic node (of Lund), pericholedochal node, retroportal node, foramen of Winslow node, superior retropancreaticoduodenal node, and posterior pancreaticoduodenal node. [ 14 ] Regional lymph nodes for perihilar bile duct malignancy are those in the hepatoduodenal ligament: Hilar, cystic node, pericholedochal, hepatic artery node, and retroportal node.…”
Section: Radiologic Anatomy Of Hdl and Portal Hepatismentioning
confidence: 99%